Zinc-finger protein CNBP alters the 3-D structure of lncRNA Braveheart in solution - Doo Nam Kim (Nature Portfolio, 2020)
Many RNA systems possess highly ordered 3-D structures that are essential to their function. Here the authors demonstrate that the long non-coding RNA Braveheart possesses a flexible but defined 3-D structure which is remodeled upon binding the protein CNBP.